COLLABORATIVE PROBLEM SOLVING MENGGUNAKAN DECISION MAKING PROBLEM BERBANTUAN VIRTUAL LABORATORY DI MTSN 9 KEDIRI - Yusal, Yulianti; Maiyanti, Azizah Anggi; Septiarini, Rizki Dwika; Sari, Rahmawati Yanita; Laili, Eva Alvi (Guru Membangun, 2024)
One of the skills needed to face challenges and competition in the 21st century is decision making skills. This skill is important because in many complex situations, the ability to make appropriate and effective decisions  is  necessary. This research aims to find out how collaborative problem solving uses virtual laboratory-assisted decision making problems to train decision making skills. The method used was pre-experimental with one group pretest-posttest design. The research subjects were 40 students at MTsN 9 Kediri. The research instrument used is a decision making skill test in the form of a description consisting of indicators for determining criteria, explaining the advantages and disadvantages of each option, creating a decision matrix, and determining choices. The results of the analysis of the average N-gain value show a value of 0.73, meaning that students' decision making skills are in the high category. Thus, it can be concluded that collaborative problem solving using decision making problems assisted by a virtual laboratory is effective in improving students' decision making skills.